Tissue-engineered human 3D model of bladder cancer for invasion study and drug discovery. (November 2017) - Ringuette Goulet, Cassandra; Bernard, Geneviève; Chabaud, Stéphane; Couture, Amélie; Langlois, Alexandre; Neveu, Bertrand; Pouliot, Frédéric; Bolduc, Stéphane
Abstract: The tumour microenvironment is critical to both the initiation and maintenance of tumorigenesis. Reconstitution of the microenvironment is a major challenge for in vitro cancer models. Indeed, conventional 2D culture systems cannot replicate the complexity, diversity and dynamic nature of the tumour microenvironment. In this study, we have developed a 3D endotheliazed vesical equivalent by using tissue engineering from primary human cells in which non-invasive or invasive bladder cancer (BCa) cell lines, cultured as compact spheroids, were incorporated. Invasive BCa cells cross the basement membrane and invade the stromal compartment whereas non-invasive BCa cells are confined to the urothelium. Our 3D BCa model could be used as a reliable model for assessing drug responses, potentially reducing or partially replacing animal experiments, and thus should have applications in the identification of novel targets as well as toxicological evaluation of anti-cancer therapies.